Genetic Effects - Kärkkäinen, Katri; Kujala, Sonja T.; Garcia-Gil, Rosario; Steffenrem, Arne; Sonesson, Johan; Hoikkala, Liina; Mäkinen, Harri; Valkonen, Sauli (Springer Nature Switzerland, 2025)
Genetic effects of continuous cover forestry (CCF) are not well known. We need more research, especially on the genetics of spruce-dominated CCF sites. Levels of relatedness are of interest, as are estimates of safe limits for the intensity and duration of CCF practices that secure genetic potential for good growth and quality. Based on research in other regions, the number of reproducing trees must be kept large to avoid excessive levels of relatedness and inbreeding and to maintain sufficient levels of genetic diversity. In some well-documented long-term experiments in other regions, intensive high-grading has led to slower growth rates, which could partly be due to genetic degradation of the stand. If contemporary recommendations for selection cutting are followed, negative genetic effects should be unlikely. With even-aged forestry, genetically improved regeneration material can be used to mitigate climate change-related risks through breeding and deployment recommendations. In CCF, currently based on natural regeneration, we assume that enough seedlings establish, and that sites contain enough genetic variation to enable natural selection and evolutionary processes.
Keywords: continuous cover forestry; genetic diversity; inbreeding; selection; growth potential